Research on remote control algorithm for parallel implicit domain robot patrol inspection on 3D unstructured grid - Li, Tingyang; Song, Yinghua; Xia, Xiaotang (Journal of ambient intelligence and humanized computing, 2020)
Aiming at the disadvantages of structural meshes that are difficult to deal with complex shapes and unstructured meshes, it is impossible to calculate the viscous flow with boundary layers. A parallel implicit algorithm based on three-dimensional unstructured meshes is developed. The turbulence model adopts the k − π turbulence model. Due to the difficulty of the LU-SGS parallel equivalent model in time advancement, a three-dimensional unstructured grid DSMC parallel algorithm is proposed. Under the unstructured grid dynamic partitioning strategy, each sub-area is guaranteed. The number of molecules is roughly equal. Based on the implicit algorithm of DP-LUR (data-parallel lower–upper relaxation) format, the remote control combination model of robot inspection is calculated, and the mutual interference flow problem during the inspection process is accurately simulated. The operator realizes the remote control of the inspection robot through the live image transmitted by the network. The actual operation shows that the system can remotely access the service system and message transmission of the inspection robot in the state of the sub-structure grid, and successfully solve the robot tour. Check the complex shape viscous flow field calculation and efficiency problems that are difficult to handle in remote control systems.